Les difficultés de la lecture chez les apprenants de5AP : Constat et remédiation Cas des élèves de la 5 AP, Ecole primaire : Riahi Mohammed El Arbi la Willaya de Souk Ahras. - Hessainia Soumia (My University, 2025)
Abstract Reading is a key skill in French as a Foreign Language (FFL), essential for the development of Algerian students from primary school onwards. In 5th grade primary (5AP), despite the competency-based approach, difficulties in fluency, comprehension, and reading strategies persist. The study at Riahi Med Larbi School (Souk Ahras) reveals various obstacles: linguistic, cognitive, affective, and sociocultural. Teachers make efforts but sometimes lack differentiation and reading-for-pleasure approaches. Effective strategies include guided reading, interactive reading, and comprehension workshops. Success requires continuous training, family involvement, and improvement of the educational framework. Adapted assessment and motivation are also essential. These approaches strengthen students' reading skills ---------------- اﻟﻤﻠﺨﺺ اﻟﻘﺮاءة ﻣﮭﺎرة أﺳﺎﺳﯿﺔ ﻓﻲ اﻟﻠﻐﺔ اﻟﻔﺮﻧﺴﯿﺔ ﻛﻠﻐﺔ أﺟﻨﺒﯿﺔ، وھﻲ ﺿﺮورﯾﺔ ﻟﺘﻄﻮﯾﺮ اﻟﺘﻼﻣﯿﺬ اﻟﺠﺰاﺋﺮﯾﯿﻦ ﻣﻨﺬ اﻟﻤﺮﺣﻠﺔ اﻻﺑﺘﺪاﺋﯿﺔ. ﻓﻲ اﻟﺴﻨﺔ اﻟﺨﺎﻣﺴﺔ اﺑﺘﺪاﺋﻲ )5ب(، وﻋﻠﻰ اﻟﺮﻏﻢ ﻣﻦ اﻟﻤﻘﺎرﺑﺔ ﺑﺎﻟﻜﻔﺎءات، ﺗﺴﺘﻤﺮ اﻟﺼﻌﻮﺑﺎت ﻓﻲ اﻟﻘﺮاءة اﻟﻤﺴﺘﺮﺳﻠﺔ واﻟﻔﮭﻢ واﺳﺘﺮاﺗﯿﺠﯿﺎت اﻟﻘﺮاءة. ﺗﻜﺸﻒ اﻟﺪراﺳﺔ ﻓﻲ ﻣﺪرﺳﺔ رﯾﺎﺣﻲ ﻣﺤﻤﺪ اﻟﻌﺮﺑﻲ )ﺳﻮق أھﺮاس( ﻋﻦ ﻋﻮاﺋﻖ ﻣﺘﻨﻮﻋﺔ: ﻟﻐﻮﯾﺔ وﻣﻌﺮﻓﯿﺔ ووﺟﺪاﻧﯿﺔ واﺟﺘﻤﺎﻋﯿﺔ ﺛﻘﺎﻓﯿﺔ. ﯾﺒﺬل اﻟﻤﻌﻠﻤﻮن ﺟﮭﻮداً، ﻟﻜﻨﮭﻢ ﯾﻔﺘﻘﺮون أﺣﯿﺎﻧﺎً إﻟﻰ اﻟﺘﻤﺎﯾﺰ واﻟﻘﺮاءة اﻟﻤﻤﺘﻌﺔ. ﺗﺘﻀﻤﻦ اﻻﺳﺘﺮاﺗﯿﺠﯿﺎت اﻟﻔﻌﺎﻟﺔ اﻟﻘﺮاءة اﻟﻤﻮﺟﮭﺔ واﻟﺘﻔﺎﻋﻠﯿﺔ وورش اﻟﻔﮭﻢ. ﯾﺘﻄﻠﺐ اﻟﻨﺠﺎح اﻟﺘﻜﻮﯾﻦ اﻟﻤﺴﺘﻤﺮ وإﺷﺮاك اﻷﺳﺮة وﺗﺤﺴﯿﻦ اﻹطﺎر اﻟﺘﻌﻠﯿﻤﻲ. اﻟﺘﻘﯿﯿﻢ اﻟﻤﺘﻜﯿﻒ واﻟﺪاﻓﻌﯿﺔ ﺿﺮورﯾﺎن أﯾﻀﺎً. ھﺬه اﻟﻤﺤﺎور ﺗﻌﺰز ﻣﮭﺎرات اﻟﻘﺮاءة ﻟﺪى اﻟﺘﻼﻣﯿﺬ ---------------------- Résumé La lecture est une compétence clé du FLE, essentielle au développement des élèves algériens dès le primaire. En 5AP, malgré l’approche par compétences, les difficultés en fluidité, compréhension et stratégies de lecture persistent. L’étude à l’école Riahi Med Larbi (Souk Ahras) révèle des obstacles variés : linguistiques, cognitifs, affectifs et socioculturels. Les enseignants font des efforts, mais manquent parfois de différenciation et de lecture-plaisir. Les stratégies efficaces incluent lecture guidée, interactive et ateliers de compréhension. La réussite passe par la formation continue, l’implication familiale et l'amélioration du cadre éducatif. L'évaluation adaptée et la motivation sont aussi essentielles. Ces leviers renforcent les compétences en lecture des élèves
Keywords: Reading; FFL (French as a Foreign Language); 5AP (5th grade primary); comprehension; fluency; academic difficulties; pedagogical strategies; remediation; competency-based approach; motivation; guided reading; continuous training; educational environment; ﻟﻘراءة، اﻟﻠﻐﺔ اﻟﻔرﻧﺳﯾﺔ ﻛﻠﻐﺔ أﺟﻧﺑﯾﺔ، اﻟﺳﻧﺔ اﻟﺧﺎﻣﺳﺔ اﺑﺗداﺋﻲ، اﻟﻔﮭم، اﻟطﻼﻗﺔ، اﻟﺻﻌوﺑﺎت اﻟﻣدرﺳﯾﺔ، اﻻﺳﺗراﺗﯾﺟﯾﺎت اﻟﺑﯾداﻏوﺟﯾﺔ، اﻟﻣﻌﺎﻟﺟﺔ اﻟﺑﯾداﻏوﺟﯾﺔ، اﻟﻣﻘﺎرﺑﺔ ﺑﺎﻟﻛﻔﺎءات، اﻟداﻓﻌﯾﺔ، اﻟﻘراءة اﻟﻣوﺟﮭﺔ، اﻟﺗﻛوﯾن اﻟﻣﺳﺗﻣر، اﻟﺑﯾﺋﺔ اﻟﺗﻌﻠﯾﻣﯾﺔ; Lecture; FLE; 5AP; compréhension; fluidité; difficultés scolaires; stratégies pédagogiques; remédiation; approche par compétences; lecture guidée; formation continue; environnement éducatif